Analisis Sentimen Masyarakat terhadap Pelayanan e-KTP dengan Metode Support Vector Machine - Elisabeth Lusi Tania Holo; Yulius Nahak Tetik; Diana Reby Sabawaly (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The rapid development of information and communication technology allows society to access various information needed in daily life. The Law of the Republic of Indonesia Number 23 of 2006 concerning population administration serves as an important element in population management. Population documents are issued by official institutions and have legal legitimacy as valid evidence. The method used in this research regarding public sentiment towards e-ID card services is the survey method, which aims to collect data from a large population using a smaller sample. The steps or processes in this research using the SVM method consist of case folding, cleaning, tokenizing, normalization, stopword removal, and stemming. Based on the classification of 150 test data using SVM, the number of positive sentiments recorded is 110 opinions, while negative sentiments recorded are 40 opinions.